Teneriffe, an Astronomer's Experiment Or, Specialities of a Residence Above the Clouds - Smyth, Charles Piazzi (Cambridge library collection. Astronomy, 1858)
The experiences and challenges undertaken by C. Piazzi Smyth during his expedition to Tenerife on behalf of the Astronomer Royal are richly depicted and illustrated in this descriptive report of a major scientific expedition's course. The experiment was 'to ascertain how far astronomical observation can be improved, by eliminating the lower third part of the atmosphere'. This account of the data collection process details the flexibility and adjustments that were required throughout the course of this experiment, and the practical organisational difficulties and delights of leading such an expedition. The joys and interest of travelling in a foreign land are described with anecdotes of the people, flora, fauna and geography; particularly the research area, a volcano. Although first published in 1858 this detailed account of the experience of collecting precise scientific data in a challenging environment provides fascinating insights for any scientist undertaking research in the wild